Long‐term clinical safety of clindamycin and rifampicin combination for the treatment of hidradenitis suppurativa. A Critically Appraised Topic. (1st April 2019) - Albrecht, J.; Baine, P.A.; Ladizinski, B.; Jemec, G.B.; Bigby, M.
Summary: Clinical question/scenario: Can therapy with clindamycin and rifampicin be safely continued long term beyond the recommended 10‐week course? Background: Clindamycin and rifampicin are used in combination to treat hidradenitis suppurativa (HS). There is no data on the efficacy and safety of clindamycin/rifampicin combination therapy for HS beyond 10 weeks. Methods: We identified the following major concerns that still lack a proper evidenced‐based analysis: for rifampicin, drug‐induced liver injury, interstitial nephritis, drug interaction and hepatic p450 3A4 enzyme induction; for clindamycin, the concern was community‐acquired Clostridium difficile infection (CA‐CDI); and experience with long‐term treatment. Data sources were used as appropriate to answer the question. Systematic searches were used to assess the risk of CA‐CDI and experience with long‐term treatment with clindamycin. Results/identified evidence: The risk for rifampicin‐induced liver injury is highest in the first 6 weeks of treatment, whereas interstitial nephritis is primarily observed during intermittent treatment. Enzyme induction due to rifampicin is usually complete after about 2 weeks of treatment and reduces clindamycin blood levels by about 90%. Three meta‐analyses identified antibiotic use as a risk factor for CA‐CDI. Two of them assigned the highest risk to clindamycin. None of them stratified by length of treatment. There is extensive experience with rifampicin, primarily for the treatment of tuberculosis. Long‐term experience with clindamycin is limited. Discussion and recommendation for clinical care: The analysed risks associated with a combination of clindamycin and rifampicin for hidradenitis suppurative cluster within the first 10 weeks. Treatment can be continued beyond 10 weeks, if clinically necessary.